2015
DOI: 10.1172/jci83279
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers on patient T cells diagnose active tuberculosis and monitor treatment response

Abstract: A r t i c l e A m e n d m e n t s 3 7 2 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 0 publications
9
22
0
Order By: Relevance
“…We first compared the activation profile of IFN-g 1 Mtbspecific CD4 1 T cells between the four groups ( Figure 1A). As previously shown (5), in HIV-uninfected persons, HLA-DR, Ki67, and CD38 expression on IFN-g 1 Mtb-specific CD4 1 T cells was significantly higher in aTB participants than in those with LTBI ( Figure 1B). Interestingly, although HLA-DR expression on Mtb-specific CD4 1 T cells in the LTBI/HIV 1 group (median, 41.7%; IQR, 25.7-54.6%) was significantly higher than in the LTBI/HIV 2 group (median, 13.7%; IQR, 8.9-27.5%), HLA-DR expression on these cells was significantly further increased in HIV-infected individuals with aTB (median, 84%; IQR, 73.7-87.9%) ( Figure 1B).…”
supporting
confidence: 78%
“…We first compared the activation profile of IFN-g 1 Mtbspecific CD4 1 T cells between the four groups ( Figure 1A). As previously shown (5), in HIV-uninfected persons, HLA-DR, Ki67, and CD38 expression on IFN-g 1 Mtb-specific CD4 1 T cells was significantly higher in aTB participants than in those with LTBI ( Figure 1B). Interestingly, although HLA-DR expression on Mtb-specific CD4 1 T cells in the LTBI/HIV 1 group (median, 41.7%; IQR, 25.7-54.6%) was significantly higher than in the LTBI/HIV 2 group (median, 13.7%; IQR, 8.9-27.5%), HLA-DR expression on these cells was significantly further increased in HIV-infected individuals with aTB (median, 84%; IQR, 73.7-87.9%) ( Figure 1B).…”
supporting
confidence: 78%
“…The presence of interleukin-2 (IL-2) cytokine-secreting CD4 ϩ T cells has been shown to correlate with bacterial burden and clinical disease (78,79). People with active TB disease also have a more activated and proapoptotic phenotype of antigen-specific CD4 ϩ T cells than people with LTBI (80,81). Th17-type CD4 ϩ T cell responses may be associated with a lower risk of progression to TB (67).…”
Section: Immune Correlates Of Incipient and Subclinical Tuberculosismentioning
confidence: 99%
“…However, the attenuated T cell response to ESAT‐6 stimulation in M. africanum infected individuals has been shown to affect the interpretation of IGRA results . In addition, a number of studies have reported that activated T cell markers and soluble cytokines can be used as reliable biomarker for monitoring the anti‐TB treatment response. It has been shown that the production of 27 proinflammatory and regulatory cytokines in response to ESAT‐6/CFP‐10 stimulation was not significantly different between M. africanum and Mtb‐infected patients pre‐treatment.…”
Section: Translational Implications Of Mtbc Lineage Associated Variatmentioning
confidence: 99%